Aerobic Tetrazine‐Catalyzed Oxidative Nitroso‐Diels‐Alder Reaction of N‐Arylhydroxylamines with Dienecarbamates: Access to Functionalized 1, 6‐Dihydro‐1, 2‐oxazines. Issue 21 (24th September 2019) - Le, Tuan; Courant, Thibaut; Merad, Jérémy; Allain, Clémence; Audebert, Pierre; Masson, Géraldine
Abstract: A new organocatalytic and environmentally friendly aerobic oxidative‐catalyzed nitroso‐Diels‐Alder (NDA) reaction of N‐arylhydroxylamines with dienecarbamates has been developed. 3, 6‐Bis(2, 2, 2‐trifluoroethoxy)‐ s ‐tetrazine was found to be an effective catalyst to selectively oxidize various N ‐arylhydroxylamines in the presence of molecular oxygen, but in the absence of photostimulation, as a terminal oxidant. In addition, active catalytic species can be generated in situ from commercially available 3, 6‐dichlorotetrazine. Abstract : Organocatalysis : New s ‐tetrazine derivatives were revealed to be effective organocatalysts for the oxidative nitroso‐Diels‐Alder (NDA) reaction of N‐arylhydroxylamines with dienecarbamates. Using molecular oxygen as a terminal oxidant, a series of functionalized 1, 6‐dihydro‐1, 2‐oxazines were prepared in moderate to good yields with excellent diastereoselectivity. This mild and eco‐friendly oxidation method is applicable to a broad substrate range.